2019
DOI: 10.1007/s00414-019-02219-6
|View full text |Cite
|
Sign up to set email alerts
|

Added value of post-mortem computed tomography (PMCT) to clinical findings for cause of death determination in adult “natural deaths”

Abstract: The aim of this study was to investigate whether post-mortem computed tomography (PMCT) provides additional information regarding the cause of death and underlying diseases in a general practitioners' (GP), out-of-hospital population. Methods and materials Bodies donated to our anatomy department between January 2014 and January 2018, who consecutively underwent a total body PMCT and had given permission for retrieval of their medical records during life, were included. PMCT scans were assessed by a radiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the pediatric population, the absence of radiological evidence of injury cannot categorically exclude abuse, neglect, and/or homicide but also can miss injuries 23,24 . In addition, postmortem radiology studies in adults have shown that postmortem radiology has limitations in recognizing both natural diseases and injuries (soft tissue, nonossified bones, and ossified bones) 22,25–30 . Thus, using postmortem radiology as a screening tool to exclude unnatural and violent deaths in infants presenting as cot death is inadequate, unreliable, and against international standards.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, the absence of radiological evidence of injury cannot categorically exclude abuse, neglect, and/or homicide but also can miss injuries 23,24 . In addition, postmortem radiology studies in adults have shown that postmortem radiology has limitations in recognizing both natural diseases and injuries (soft tissue, nonossified bones, and ossified bones) 22,25–30 . Thus, using postmortem radiology as a screening tool to exclude unnatural and violent deaths in infants presenting as cot death is inadequate, unreliable, and against international standards.…”
Section: Discussionmentioning
confidence: 99%